Alcohol and Young People: Australian Baseline Data for a W.H.O Cross-Cultural Study - Blaze-Temple, D.; Fisher, J.; Cross, D.; Howat, Peter (Drug and Alcohol Foundation Victoria, 2014)
This study is the result of a survey of 1000 year 8 students' responses o a questionnaire relating to alcohol knowledge, attitudes to alcohol use, behaviour skills, behavioural intentions and behaviour (that is consumption). These results formed the baseline data upon which the impact of a peer-led versus teacher- led versus no treatment alcohol education programme will be evaluated. The major findings were as follows a relatively high knowledge level was recorded for both boys and girls both sexes perceived themselves to be equally able to say no to an offer of a drink in a variety of situations. 3.8% of the sample were classified as problem drinkers problem drinkers were associated with a lower knowledge score early age of first drink and lower perception of their ability to say no The detection of boasting and other problems related to self-reporting are also discussed.